Effect of age, decentration, aberrations and pupil size on subjective image quality with concentric bifocal optics - Rio, David; Woog, Kelly; Legras, Richard (Ophthalmic & physiological optics, 2016)
Purpose We investigated the impact of lens centration, wearer aberrations, pupil size and age on the optics of two bifocal contact lenses using image simulation. Method Fourteen conditions (i.e. two optical profiles with two and eight concentric zones; two conditions of centration: centred and 0.77 mm decentred; and three conditions of aberrations: 0, 0.15 and 0.35 μm RMS; three pupil sizes: 3, 4.5 and 6 mm) were tested on two populations (i.e. 20–40 and 40–60 years old) using a numerical simulation method. For each condition, images were calculated for proximities ranging from ‐4D to + 2D with steps of 0.25D. Subjects graded the quality of each simulated image (i.e. a target ‘HEV’ of 0.4 logMAR) on a continuous scale from 0 to 5. To limit the effect of the observer's own aberrations, subjects viewed the displayed images through a 3‐mm pupil and their optimal correction. Results Both populations reported similar image quality (i.e. average absolute difference of 0.23) except for sharp and low contrast images, which obtained slightly higher grades with younger subjects, probably due to a better contrast sensitivity in this population. Typical decentration had no effect on bifocal contact lenses wearers' vision, as the ratio between areas dedicated to near and distance vision did not change. Aberrations (i.e. mainly 0.24 μm of spherical aberration on a 4.5‐mm pupil) reduced the addition of the two radial zones bifocal optics and introduced a hyperopic shift (i.e. 0.50D) of the through‐focus image quality for the eight radial zone bifocal lens. The combination of typical aberrations with typical decentration created the same effect as typical aberrations alone, meaning that aberration impact was stronger than decentration impact. The two radial zone bifocal lens was dependent on the pupil whereas the eight radial zone lens was not. Conclusions When fitting new bifocal optics, the aberrations of the patients, as well as their pupil diameter, are the main subject dependent parameters influencing quality of vision. Typical contact lens decentration and lower cortical treatment efficiency of retinal images of older subjects had relatively little impact.